Nonlinear Deterministic Study of Seismic Microzoning of a City in North of Algeria - Badreddine Bousbia; Badreddine Sbartai (Salehan Institute of Higher Education, 2019)
This paper presents also an overview of seismic microzonation studies of the city of Mohammadia-Algiers, which are important for a detailed ground movement modeling of urban cities. According to the seismic history of the city, one extraordinary earthquake event has been taken into consideration is Boumerdes earthquake (Algeria, May 21, 2003, magnitude Mw=6.5), that caused a huge damage. Thereby, the variability prediction of the seismic ground movement in a given built-up area, it is considered as an effective tool for planning appropriate urban development and understanding both seismic risk and damage pattern, caused by a strong movement event. We note that the shaking level is mainly described in terms of both maximum ground acceleration and visualized amplification by using response spectra. The study is carried out in two steps: - a detailed mapping of the geology and geotechnical properties of the area - numerical modeling of expected ground motions during earthquakes. A qualitative microzonation of the Mohammadia-Algiers city is presented, and it is discussed by comparing it to the historically reported damage of the 2003 Boumerdes earthquake. Finally, this study deals with the seismic microzonation map development, based on a SIG geological model.